School-Based Management in Adiwiyata Elementary School, Banyumas - Agung Nugroho; Karma Iswasta Eka; Nur Aini Hidayah (Jurnal Elementaria Edukasia, 2023)
The authority to run and decide on a program is the key to implementing school-based management (SBM). This study aims to describe the implementation of a school-based management program at SD Negeri Kedondong as an Adiwiyata elementary school in Banyumas Regency. This research is qualitative research where the data in this research were obtained by means of interviews, observation, and documentation. The data were then analyzed using source triangulation techniques and technical triangulation. The research results show that the implementation of SBM in SD Negeri Kedondong can be said to be going well. MBS stages include; 1) stages of exploring school potential, 2) forming a management team, 3) collaborating with related parties, 4) implementation of SBM, and 5) evaluation of activities.